ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBENTUKAN KARAKTER SISWA DI ERA DIGITAL: KAJIAN BERBASIS KERANGKA ETIKA DIGITAL PANCASILA - Dhiyaa' Rihhadatul 'Aisy; Chamelia Bunga Nurani; Ahmad Syaiful Ghozi; Imam Junaris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study offers a novelty in the form of the Pancasila Digital Ethics (PDE) conceptual framework, formulated from the synergy of three Merdeka Curriculum instruments: the Pancasila Student Profile Strengthening Project (P5), the Student Centered Learning (SCL) approach, and the six dimensions of the Pancasila Student Profile as an integrated moral defense system for students in the digital era. Unlike previous studies that examined these aspects separately, this research integrates them into a cohesive model operationalizable as a curriculum implementation evaluation instrument. The qualitative library research method employs descriptive-analytical analysis in three stages: data reduction, conceptual synthesis, and framework construction. Three main findings emerge: (1) P5 flexibility operates as a value contextualization mechanism that actively translates Pancasila principles into concrete responses to real digital challenges; (2) SCL builds critical reasoning not merely as a cognitive competency but as an intrinsic digital filter working autonomously without external oversight a new conceptualization surpassing previous studies; and (3) the six Pancasila Student Profile dimensions operate as an integrated moral compass system with layered functions foundation, moderation, actualization, regulation, filter, and transformation producing ethically resilient digital agents. These findings are synthesized into the PDE Framework offering dual contributions: theoretically enriching character education discourse grounded in national cultural values, and practically providing an operationalized instrument for evaluating Merdeka Curriculum implementation.